A NARRATIVE OF AN INDONESIAN PRE-SERVICE ENGLISH TEACHER’S EMOTIONS IN INTERNATIONAL TEACHING PRACTICUM - Ninik Tri Astutik; Willy Prasetya (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2021)
International teaching practicum (ITP) has gained more popularity since it is considered as a way of improving teachers’ quality not only in terms of the pedagogical competence but also the intercultural one. Despite the growing body of research on emotions of pre-service English teachers as well as on ITP experiences, little attention has been given to the role of emotions particularly in pre-service teachers’ ITP experiences. Therefore, drawing on the notion of structures of feeling by Williams (1977), the present study attempted to explore an Indonesian pre-service English teacher’ emotions during her participation in an ITP program in Thailand. The narrative of the pre-service teacher was collected through semi-structured interviews, follow-up conversations and online correspondences. Thematic analysis was then conducted to analyze the narratives. The result of this study shed light on how interaction with students and co-workers as well as with sociocultural differences affected the participant’s emotions and how emotions shaped her thoughts, beliefs, and actions as teachers. The implication of this study is also discussed.